2009
DOI: 10.1055/s-0029-1185361
|View full text |Cite
|
Sign up to set email alerts
|

Can Rhizoma Chuanxiong Replace Radix Angelica Sinensis in the Traditional Chinese Herbal Decoction Danggui Buxue Tang?

Abstract: Herein, we test the hypothesis that a member of a formulated Chinese herbal decoction cannot be replaced by another herb. Danggui Buxue Tang (DBT) is being used as an example for illustration: this is a traditional decoction containing Radix Astragali (RA) and Radix Angelicae Sinensis (RAS) in a weight ratio of 5 to 1. Rhizoma Chuanxiong (RC) and RAS are two chemically very similar herbs but with a distinct function. Following the preparation method of DBT, a herbal decoction, namely Chuanxiong Buxue Tang (CBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…When relating any modernised CHM extract to the long experience of TCM it should be considered that its clinical efficacy should at least match the one of the traditional preparation it relates to. It has been shown that the single active markers that are typically used for the quality control of herbal drugs may not be able to fully explain a product's quality, especially when the drug is used as part of a co-extracted herbal mixture (Schmid et al, 2001;Li et al, 2009;Vlietinck et al, 2009), and frequently not even an active marker is known but analytical markers without known clinical relevance are used as a surrogate. As a consequence, such single markers cannot be generally recommended to guide the optimisation of an extract.…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…When relating any modernised CHM extract to the long experience of TCM it should be considered that its clinical efficacy should at least match the one of the traditional preparation it relates to. It has been shown that the single active markers that are typically used for the quality control of herbal drugs may not be able to fully explain a product's quality, especially when the drug is used as part of a co-extracted herbal mixture (Schmid et al, 2001;Li et al, 2009;Vlietinck et al, 2009), and frequently not even an active marker is known but analytical markers without known clinical relevance are used as a surrogate. As a consequence, such single markers cannot be generally recommended to guide the optimisation of an extract.…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…All of those medicinal materials were purchased from Guangzhou Zixing Herbal Company in Guangzhou at June in 2013 by Liu Jing and they are identified by Prof. Chen Hu-Biao. The following reference compounds: (6aR,11aR)-3-hydroxy-9,10-dimethoxypterocarpan (astrapterocarpan), ononin, formononetin, 6''- O -acetyl-ononin, calycosin, ferulic acid, (3R)-7,2'-dihydroxy-3',4'-dimethoxyisoflavan (astraisoflavan), calycosin-7- O - β - d -glucoside, astrapterocarpan-7- O - β - d -glucoside, Z -ligustilide, E -ligustilide, astragaloside I, astragaloside II, astragaloside III, astragaloside IV, astragaloside V, astraisoflavan-7- O - β - d -glucoside and 6''- O -acetyl-astraisoflavan-7- O - β - d -glucoside were prepared and identified in our preliminary work [10,11,12,13,14]. Acetonitrile (Merck Co., Darmstadt, Germany) and formic acid (Mreda Technology Inc., Beijing, China) were of HPLC grade.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Radix Hedysari (RH) has been used to replace RA. Thus, in current clinical applications, DBT is prescribed in two forms: RA:RAS (5:1) (called DBT1), and RH:RAS (5:1) (called DBT2) [1,10].…”
Section: Introductionmentioning
confidence: 99%